Advanced cutaneous squamous cell carcinoma: real world data of patient profiles and treatment patterns. (28th October 2019) - Amaral, T.; Osewold, M.; Presser, D.; Meiwes, A.; Garbe, C.; Leiter, U.
Abstract: Background: Cutaneous squamous cell carcinoma (cSCC) is one of the most common types of cancer in the Caucasian population, with an increasing incidence. cSCC is mostly a local invasive disease that can be treated surgically in the majority of the cases. However, in the case of advanced cSCC (acSCC), a multimodality approach also involving systemic therapies needs to be considered. Methods: One hundred and ninety‐five patients diagnosed with acSCC (stages III and IV) treated in our centre between 2011 and 2018 were included. Patient and tumour characteristics along with treatment patterns were documented and analyzed. Descriptive analysis was performed and survival rates were estimated according to Kaplan‐Meier and compared with the Log‐rank test. Follow‐up was defined as the time between diagnosis of advanced disease and last contact or death. All causes of death were considered as events. Results: The median follow‐up was 21 months [IQR = (10.0; 21.0)]. The median age at time of advanced disease diagnosis was 78 years [IQR = (72; 84)], with 40.5% of the patients in stage III and 59.5% in stage IV. One hundred and forty‐five patients had resectable tumours. In this group the median overall survival (mOS) was 59 months (95% CI: 28.2–89.8), significantly higher than the mOS in patients with inoperable tumour [ n  = 50; mOS: 19 months (96% CI: 7–31, P  <0.0001)]. Patients receiving immunotherapy ( n  = 20) showed a statistically significant better survival compared to those treated with other systemic therapies ( n  = 37; mOS not reached vs. mOS: 22 months (95% CI: 6.5–43.5), P  =   0.034). For patients without systemic therapy, a combination of surgery and radiotherapy provided better outcomes compared to radiotherapy alone or best supportive care ( P  <0.001). Conclusion: Surgical complete resection should be the first therapeutic option for patients with acSCC. For patients with inoperable tumour, first‐line immunotherapy should be preferably considered.